Exploring the emotion regulation strategies used by adults with intellectual disabilities. (27th May 2018) - Littlewood, Mark; Dagnan, Dave; Rodgers, Jacqui
Abstract : Objectives: There is a growing body of evidence revealing emotion regulation difficulties are a common factor in the development and maintenance of mental health problems in the general population, however relatively little is known of the emotion regulation strategies used by people with intellectual disabilities. Method: A qualitative approach was used to explore the emotion regulation strategies used by adults with a mild intellectual disability in interpersonal experiences. Semi-structured interviews were conducted with 11 participants with the transcripts analyzed using Thematic Analysis. Results: Three main-themes, each with two sub-themes were identified; regulatory talk (sub-themes of 'self-talk' and 'talking about emotions in beneficial'), avoidance (sub-themes of 'avoidance is bad' and 'avoidance can be good') and cognitive strategies (sub-themes of 'cognitive distraction' and 'cognitive reappraisal'). Conclusions: The main-themes and sub-themes suggest people with intellectual disabilities can use a range of strategies in different contexts. Research and clinical implications are discussed.